On some spectral properties of third order nonlinear boundary value problems - Smirnov, Sergey (Mathematical Modelling and Analysis, 2012)
The present paper deals with a two point the third-order nonlinear boundary value problem. An estimation of the number of solutions to boundary value problem and their nodal structure are established. Some results are given on spectral properties of solutions.